A produção dos lugares discursivos e ideológicos em uma ocupação urbana: contribuições da psicanálise clínico-política - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Historically occupation has been one of the ways to solve the impasses regarding the right to housing in terms of the demands of the population and the insufficient answers or solutions presented by the State. Amazonas is the Brazilian state with the third highest housing deficit, being a place where the housing problem requires profounder study in different areas of knowledge. In the state capital of Manaus, in 2015, residents of the Cidade das Luzes [City of Lights] a community defined as an irregular occupation, suffered involuntary violent removal. Among the subsequent developments in 2016, a group of families that had been evicted, and neglected by the State, were led by a social movement to occupy an unused building belonging owned by the State in the City centre. In this work we call the condition in which the inhabitants of the Alcir Matos occupation are still unassisted by the authorities sociopolitical and discursive helplessness. We consider the dimension of suffering experienced by these residents throughout their struggle for the right to housing, taking the problem of how they are inscribed in the social and political scene and in which discursive and ideological places of reproduction or production of places, in the subject’s relation to the social ties they have been able to build. Through implied psychoanalysis, or clinical-political psychoanalysis, we attempt to understand the ideological discursive places in the context of an Urban Occupation, in order to comprehend how the incidence of discourse mobilises, affects and composes the everyday life of its inhabitants. The material analysed consisted of the notes of a research field journal produced from the diverse modalities of the researcher’s participation in the daily contact with the residents, and of data resulting from documentary research on the media production around the Occupations. In the results, we highlight an area of tensions, impasses and conflicts that are part of the daily life of the Occupation, but which also indicate relations between trauma, experience and the subject’s condition of wandering and desiring that is made and unmade in contemporary social bonds. Resistance is perceived, in a different way from the sense of avoidance, as a resource of struggle and a demarcator of existence in the discursive plane. It is concluded that there is a lack of means to listen to the subjects, in order to enable the transformation of the traumatic event into a shared experience and that also strengthens forms of community life. To this end, strategies for intervention with communities living in urban occupations, or in other conditions of exclusion or marginalisation, that are aimed at the production and practise of these conditions, may be effective. We see this way as a possibility to resist the hegemonic discourses that are totalising, naturalising oppression and criminalising poverty and transforming the right to decent housing into an illusion.
The production of discursive and ideological places in an urban occupation: contributions of clinical-political psychoanalysis
Keywords: Psicologia comunitária; Psicanálise; Habitação - Manaus (AM); Direito à moradia; CIÊNCIAS HUMANAS: PSICOLOGIA; Psicanálise clínico-política; Lugares discursivos; Ocupações urbanas; Psicologia comunitária